Correction: Speaking out of turn: How video conferencing reduces vocal synchrony and collective intelligence. - Maria Tomprou; Young Ji Kim; Prerna Chikersal; Anita Williams Woolley; Laura A Dabbish (PLoS ONE, 2023)
[This corrects the article DOI: 10.1371/journal.pone.0247655.].